Picea abies network: Report of the 1st meeting, 16-18 March 1995, Tatra National Park, Starà Lesnà, Slovakia - Turok, J.; Koski, V.; Paule, L.; Frison, Emile A.; European Forest Genetic Resources Programme (1995)
This report of the first European Forest Genetic Resources Programme (EUFORGEN) meeting on the P. abies network includes summaries of the outcome of discussions on the following areas: definition of objectives of the P. abies network; descriptors and database for P. abies; current criteria for selection of populations for genetic conservation; identification of common research needs; and identification of contact persons in all countries. Six network tasks that were agreed and a workplan that was developed during the meeting are outlined. The 14 papers presented at the meeting are provided, including reports on the status of P. abies genetic resources conservation work in Finland, Latvia, Lithuania, Poland, Austria, Switzerland, Belgium, Slovakia, Ukraine, Norway, Germany, Denmark and the Czech Republic, as well as forest genetic resources activities of the Food and Agriculture Organization. (Abstract © CAB ABSTRACTS, CAB International)